Boron & Boulpaep concise medical physiology - Walter F. Boron (Author); Emile L. Boulpaep (Author) (Philadelphia, PA, Elsevier, 2021)
"Medical students and faculty have long looked to Boron & Boulpaep$1 (Bs Medical Physiology for an unparalleled, comprehensive understanding of complex human physiology. By popular demand, the new Boron & Boulpaep Concise Medical Physiology offers Boron & Boulpaep$1 (Bs authoritative content in a condensed, entry-level presentation that is well-illustrated and student friendly. You$1 (Bll find the same trusted quality and attention to detail as the parent text, with a logically organized format, clear, instructive figures, and online animations -- all focused on the essential information you need to know for a solid introduction or a quick review."s
In English
Keywords: Human physiology